(3a+2)(3a-1)=0

Simple and best practice solution for (3a+2)(3a-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3a+2)(3a-1)=0 equation:


Simplifying
(3a + 2)(3a + -1) = 0

Reorder the terms:
(2 + 3a)(3a + -1) = 0

Reorder the terms:
(2 + 3a)(-1 + 3a) = 0

Multiply (2 + 3a) * (-1 + 3a)
(2(-1 + 3a) + 3a * (-1 + 3a)) = 0
((-1 * 2 + 3a * 2) + 3a * (-1 + 3a)) = 0
((-2 + 6a) + 3a * (-1 + 3a)) = 0
(-2 + 6a + (-1 * 3a + 3a * 3a)) = 0
(-2 + 6a + (-3a + 9a2)) = 0

Combine like terms: 6a + -3a = 3a
(-2 + 3a + 9a2) = 0

Solving
-2 + 3a + 9a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(-2 + -3a)(1 + -3a) = 0

Subproblem 1

Set the factor '(-2 + -3a)' equal to zero and attempt to solve: Simplifying -2 + -3a = 0 Solving -2 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3a = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3a = 0 + 2 -3a = 0 + 2 Combine like terms: 0 + 2 = 2 -3a = 2 Divide each side by '-3'. a = -0.6666666667 Simplifying a = -0.6666666667

Subproblem 2

Set the factor '(1 + -3a)' equal to zero and attempt to solve: Simplifying 1 + -3a = 0 Solving 1 + -3a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3a = 0 + -1 -3a = 0 + -1 Combine like terms: 0 + -1 = -1 -3a = -1 Divide each side by '-3'. a = 0.3333333333 Simplifying a = 0.3333333333

Solution

a = {-0.6666666667, 0.3333333333}

See similar equations:

| 3a+2=3a-6 | | -5+(-15d+1)=2(7d-17)-d | | .07x+.03y=366 | | 5m+6km-8hm=m | | 15-4x=45+10x | | 8s^2-9s+2=0 | | d^2-18d+81=13 | | 5m+6km-8hm= | | =i^103 | | 4s^2-8=0 | | .66y=12 | | 24=-.33t | | .20n=-9 | | 4s^2-3s=0 | | 3(x^2-14x+49)=-14 | | 9s^2+2s-9=0 | | 3s^2-9s-6=0 | | 6(1+2x)-(8x-7)=17 | | w-11=3 | | 2(x)-8=x-7 | | 5v+25= | | 5(15x+5)=415 | | cos(x)=11x | | 7x^2+5x+h=0 | | ln(x+35)-ln(x-1)=ln(x-5) | | 6s^2+5s=0 | | 2+10(4x+5)= | | 3(x^2-14x)=-14 | | 6(-3x+4)=-120 | | .2x+.3y=.23(100) | | 5s^2-5s-7=0 | | -2s-7=5 |

Equations solver categories